Efficacy of the transvesical approach for robotic-assisted radical prostatectomy via a bladder neck and prostate combined longitudinal incision for the treatment of localized prostate cancer - Yang, YunKai; Wang, Jingyun; Zhang, DaHong; Zhang, Qi (Frontiers in Surgery, 2023)
Objective This study explores the feasibility and safety of the transvesical approach of robotic-assisted radical prostatectomy via a bladder neck and prostate combined longitudinal incision. Methods From June 2017 to May 2021, 41 patients aged from 51 to 69 years underwent the transvesical approach of robotic-assisted radical prostatectomy via a bladder neck and prostate combined longitudinal incision (L-RALP). The prostate volume was 22.0–57.8 ml (mean: 36.3 ± 11.1 ml), with a preoperative PSA value of 3.7–12.3 ng/ml (mean: 7.3 ± 1.2 ng/mL). All preoperative Gleason scores were less than or equal to 7 points, and the preoperative TNM stage ranged from T2a to T2b. All patients were diagnosed with prostate cancer by preoperative prostate biopsy or postoperative pathological specimens after prostatectomy. The operation, blood loss, hospitalization, erectile function and postoperative urinary continence were recorded. Patients were defined as continent if they answered “zero pad” per day, and they were invited to fill out The International Consultation on Incontinence Questionnaire (ICI-Q-SF) after the catheter removal at 4 and 24 weeks. Results All the operations were completed by robotic-assisted radical prostatectomy without transition to open surgery. The surgery time was 105–131 min (mean: 111.3 ± 14.9 min), with an estimated blood loss of 50–220 ml (mean: 95.5 ± 27.3 ml). The postoperative hospital stay was 3–8 days (mean: 5.2 ± 1.7 days), and the postoperative catheter was removed after 5–7 days (mean: 6.3 ± 1.1 days). After 24 weeks of follow-up, 35 cases (85.4%, 35/41) obtained immediate urinary continence after the catheter removal in 24h. All patients had regained continence 24 weeks postoperatively (100%, 41/41). Conclusion The transvesical approach of robotic-assisted radical prostatectomy via a bladder neck and prostate combined longitudinal incision is a safe and effective surgical technique, beneficial for early continence recovery and erectile function, and it is also suitable for prostate cancer patients after prostate enucleation.